“The Effect Of Profitability On Dividend Payment Through Income Smoothing As Moderator (Survey On Pharmaceutical Companies Registered In Indonesia Stock Exchanges in Period of 2015-2019)” - Irene Sukma Lestari Barus (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was performed quantitatively through explanatory approach. Secondary data from audited financial reports on pharmaceutical companies listed on the Indonesia Stock Exchange were employed and analyzed using Regression Moderation Analysis (RMA). As many as 45 samples were involved and chosen using purposive judgment sampling. The test results showed that the profitability measured by the net profit margin proxy had a significant and negative effect directly on dividend payments as measured by the dividend payout ratio. This was indicated by the significant level of the pair value of 0.0000. The effect of Income Smoothing on dividend payments was positive but not significant with a pair value of 0.8941. The effect of the interaction variable between net profit margin and income smoothing on positive dividend payments was insignificant with a pair value of 0.5768, while the influence of the net profit margin, income smoothing, and interaction variables on dividend payments had a significant and simultaneous effect by 70.81%. The interaction value is greater than 0.05, which is 0.5768, indicating that there is no moderating effect of income smoothing on the relationship between net profit margin and dividend payments. Therefore, income smoothing tends to have a positive relationship, which means that when the income smoothing variable increases, it weakens the conducive relationship with the net profit margin, but income smoothing can strengthen the relationship between dividend payments. This means that the more decrease the net profit margin, the more decrease the ability to pay dividends as well.